Penerapan Pajak Progresif Kendaraan Bermotor Terhadap Tingkat Kepemilikan Kendaraan Pribadi Dan Tingkat Kemacetan Lalu Lintas Di Indonesia - Amalia, Mia; Safira, Sahla Nazma; Irawati, Irawati; Ghanimah, Ghanimah; Mulyadi, Regina Putri Sri; Hodijah, Siti Nur (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Indonesia has experienced a dramatic surge in the number of motorized vehicles.Purposes of the Research: This study aims to analyze the impact of the implementation of progressive tax on motor vehicles on the level of private vehicle ownership and traffic congestion in Indonesia.Methods of the Research: The methodology employed is qualitative research with a normative juridical approach, resulting in descriptive data regarding the effects of progressive tax policies.Results of the Research: The findings indicate that the implementation of progressive tax in Indonesia has the potential to reduce the number of private vehicles by imposing higher rates on individuals who own more than one vehicle. Although there is a decline in the ownership of second and subsequent vehicles, challenges in socialization and public understanding remain significant obstacles. Additionally, positive impacts on traffic congestion have been observed in several regions, although this is contingent upon the development of adequate public transportation infrastructure. The study concludes that the success of progressive tax in addressing congestion and environmental pollution requires effective implementation, public support, and the development of sustainable transportation alternatives. Therefore, a holistic and integrated approach is essential to ensure maximum benefits from this policy for society and the environment